(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3jHJOF HaUd GdbGa HHGH GdJGA (B( (3bJJ(B) s
(3BNQgG (B:s
(3jfJgi HCKfGA aUd GdZjf HGH GdOGd (B( (3ZeO (B) s
(3HgG fXGe GdJYbjHIs
(3bhHdJ HNW GHf GdLhGdjbis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs